Brain drain: Propulsive factors and consequences - ILIC, Dragan; MILOSAVLJEVIC, Marko (Journal of Economic Development, Environment and People, 2018)
When speaking about the total number of highly educated individuals’ migration, it is easy to spot that it is rapidly increasing. The brain drain issues should be taken very seriously especially in under developed and in the developing countries, knowing that the human capital is globally mobile and that highly educated individuals can without any issues market their knowledge around the globe. Dealing with it requires a carefully tailored strategy for these countries, which are suffering from severe human capital losses on annual basis. Since the labor markets of today are highly competitive, it is necessary for these countries to secure good advancement and doing business opportunities. The purpose of this research is to provide an insight into the key propulsive factors and potential consequences caused by the brain drain. The method used in order to conduct the research was a carefully designed questionnaire taken by the date subject enrolled at the third and fourth years of state governed and privately owned universities. This research shows that one of the key reasons for brain drain in underdeveloped and in the developing countries is shortage of further educational advancement opportunities.